1999
DOI: 10.1073/pnas.96.8.4668
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopentenone prostaglandins suppress activation of microglia: Down-regulation of inducible nitric-oxide synthase by 15-deoxy-Δ 12,14 -prostaglandin J 2

Abstract: Mechanisms leading to down-regulation of activated microglia and astrocytes are poorly understood, in spite of the potentially detrimental role of activated glia in neurodegeneration. Prostaglandins, produced both by neurons and glia, may serve as mediators of glial and neuronal functions. We examined the inf luence of cyclopentenone prostaglandins and their precursors on activated glia. As models of glial activation, production of inducible nitric-oxide synthase (iNOS) was studied in lipopolysaccharide-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
229
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(248 citation statements)
references
References 40 publications
14
229
5
Order By: Relevance
“…Although PPARa agonists had no effect on iNOS mRNA expression, we saw a marked reduction in LPSinduced iNOS mRNA levels after treatment with 15d-PGJ 2 , a natural ligand of PPARg (Figure 4a). 15d-PGJ 2 reduced also LPS-induced iNOS protein expression and NO production (Figures 4b and c) as reported previously (Ricote et al, 1998;Petrova et al, 1999). These results suggest that the mechan-ism of the inhibitory effect of PPARa agonists on NO production is different from that of PPARg agonists.…”
Section: Effects Of Ppara Agonists On Inos Mrna Levels and Activationsupporting
confidence: 88%
“…Although PPARa agonists had no effect on iNOS mRNA expression, we saw a marked reduction in LPSinduced iNOS mRNA levels after treatment with 15d-PGJ 2 , a natural ligand of PPARg (Figure 4a). 15d-PGJ 2 reduced also LPS-induced iNOS protein expression and NO production (Figures 4b and c) as reported previously (Ricote et al, 1998;Petrova et al, 1999). These results suggest that the mechan-ism of the inhibitory effect of PPARa agonists on NO production is different from that of PPARg agonists.…”
Section: Effects Of Ppara Agonists On Inos Mrna Levels and Activationsupporting
confidence: 88%
“…PPARg-independent effects of 15-PGJ 2 have been previously reported in other systems, including chondrocytes, myofibroblasts, mesangial cells, inflammatory cells and cells of the nervous system (Petrova et al, 1999;Castrillo et al, 2000;Rossi et al, 2000;Straus et al, 2000;Boyault et al, 2001;Li et al, 2001;Janabi, 2002;Ward et al, 2002). Several mechanisms have been implicated as responsible for the effects of 15-PGJ 2 on these cells and may also partly explain its antineoplastic properties.…”
Section: Discussionmentioning
confidence: 83%
“…Negative regulation of the NF-kB pathway through inhibition of IkB kinase (IKK) and abrogation of the DNA binding ability of NF-kB, has emerged as a major pathway of PPARg-independent 15-PGJ 2 activity (Petrova et al, 1999;Castrillo et al, 2000;Rossi et al, 2000;Straus et al, 2000;Boyault et al, 2001;Janabi, 2002;). 15-PGJ 2 -mediated NF-kB inhibition has been linked to downregulation of inducible nitric oxide synthase (iNOS) and abrogation of cyclooxygenase-2 (COX-2) transactivation (Petrova et al, 1999;Castrillo et al, 2000;Rossi et al, 2000;Straus et al, 2000;Boyault et al, 2001;Janabi, 2002). Similarly, Ward et al (2002) recently showed that 15-PGJ 2 exploits PPARg-independent inhibition of NF-kB activation to induce caspase-dependent apoptosis in granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the beneficial effects microglia have in initiating protective immunity against pathogens, when chronically activated, microglia have been implicated in contributing to neuronal cell death associated with neuroinflammatory and neurodegenerative disorders. Petrova et al [41] were the first to report that the PPAR-γ agonist 15d-PGJ 2 inhibited microglial activation. They demonstrated that 15d-PGJ 2 inhibited NO production by the BV-2 mouse microglial cell line.…”
Section: Effects Of Ppar-γ Agonists On Microglial Activationmentioning
confidence: 99%